FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN PETANI KARET DI DESA BUMI SAY AGUNG KECAMATAN BUMI AGUNG KABUPATEN WAY KANAN - Tiya, Sinta Adi; Septianita, Septianita; Lastinawati, Endang (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2023)
This study aims to determine the factors that influence rubber farmers in Bumi Say Agung Village, Bumi Agung District, Way Kanan Regency. This research method was carried out using a quantitative method in which the research used multiple linear regression analysis. Data was obtained by distributing questionnaires and data obtained from rubber farmers in Bumi Say Agung Village. The results of this study are the factors that affect the income of rubber farmers in Bumi Say Agung Village, Bumi Agung District, Way Kanan Regency, namely there are six factors including: amount of production, fertilizer costs, labor costs, prices, production costs and land area. Of the six factors, four factors have a significant effect on the income of rubber farmers in Bumi Say Agung Village, namely the factors of production quantity, price, production costs and land area, and two factors that have no significant effect on the income of rubber farmers in Bumi Say Agung Village, namely the cost of fertilizer and labor costs.